Droplet coalescence at microchannel intersection chambers with different shapes. Issue 26 (14th June 2016) - Liu, Zhaomiao; Wang, Xiang; Cao, Rentuo; Pang, Yan
Abstract : The influence of microchannel intersection chamber shape on the droplet coalescence process is investigated in this study. Abstract : The influence of microchannel intersection chamber shape on the droplet coalescence process is investigated in this study. Three kinds of chamber shapes (half-round, triangle and camber) are designed to realize head-on droplet coalescence. The coalescence processes are visualized using a high-speed camera system and the internal flow patterns are resolved using a micro-PIV system. Experimental analyses on the coalescence position and coalescence time of droplets and the critical conditions are discussed. Both direct coalescence and late coalescence can be observed in the camber junction while only the late coalescence is present for the half-round and the triangle junction. The critical capillary number Ca* varies for different working systems or intersection shapes. Ca* in the camber junction is larger than that in the other two junctions for each working system and it decreases with the increase of the viscosity ratio for each intersection shape. Moreover, the characteristics of the velocity fields for different coalescence cases are analyzed for an in-depth understanding of the process.